An Innovative Approach to Remote Electronic Health Onboarding Record Education Amid a Global Pandemic. Issue 10 (29th October 2022) - Brown, Amanda; Patel, Reena; Edmister, Kathy; Gemberling, Trisha; Griffin, Erica; Kuehn, Stacy; Larson, Mary; Meyer, Jennifer; Skeens, Micah; Sunderland, Stephanie
Abstract : The COVID-19 pandemic required social and physical distancing to reduce the spread of disease. The reduction in meeting sizes made it difficult to offer traditional in-person EHR training to new and transferring employees. This paper aims to share how one nurse educator team used an innovative approach to transition traditional EHR onboarding education to synchronous remote learning during the global pandemic. Participants in the remote learning course (n = 94) were compared with those who had previously completed the traditional course (n = 110). Postcourse evaluations for each group were comparable. Remote learning participants found the technology conducive to training and reported higher scores for locating and reviewing patient information than those in the traditional course. Providing remote EHR education is comparable with traditional classroom education. Remote learning provided a safe, effective way to onboard new staff during the pandemic.